(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Crimes related to sexual violence are rarely reported to law enforcement agencies. Such crimes are multifaceted, and some details can be difficult to reveal even during a thorough investigation.